Human Versus Artificial Intelligence in Creative Physics Thinking: A Philosophical Reflection on Learning and Cognition - Sofita, Mita; Damarsha, Adrian Bagas; Prasetya, Joenathan Eka; Yuliatin, Elisa Dwi; Rahma, Nur Fitri; Jauhariyah, Mukhayyarotin Niswati Rodliyatul; Saphira, Hanandita Veda (National Dong Hwa University, 2024)
The rapid advancement of artificial intelligence (AI) has led to its increasing integration into education, including in subjects like physics that require high-level cognitive skills. This study compares human responses with those generated by AI models (ChatGPT and DeepSeek) to physics problems designed to measure creative thinking skills while exploring the philosophical patterns in AI reasoning as a reflection of human cognition. Using a qualitative-comparative method, responses were analyzed based on fluency, elaboration, originality, and flexibility, focusing on the concept of moment of inertia within the traditional